ANALISIS FIKIH MUAMALAH TERHADAP PRAKTIK JUAL BELI IKAN DI PEMANCINGAN DENGAN SISTEM JATAHAN - Adelia Putri Damaehati; Sulistyaningsih Meliana (Academica: Journal of Multidisciplinary Studies, 2020)
Buying and selling is a basic thing that must be fulfilled in buying and selling. The terms and conditions in buying and selling are people who have contract, object of sale, sale and purchase agreement, and exchange value of goods. To see the suitability between the practice of buying and selling fish in the rationed fishing system with buying and selling according to Islamic law, then using the pillars and terms of sale and purchase in Islam. This research uses interview, observation, and documentation methods. For this reason, the results will bring changes for the better.Keywords:Â buy and sell; contract; jatahan